(untitled) (Eurasian Journal of Philology Science and Education, 2024)
The article is devoted to the study of the problem of the poetic language of the constituent poetic corpus of the Kazakh language. The poetic features of the variants of the song "Kozy Korpesh – Bayan Sulu", taken as the main version, are analyzed. Examples from the poem "Kyz Zhibek" are partially given. The purpose, main direction and idea of the research is to reveal the poetic value of the variants of the poem "Kozy Korpesh – Bayan Sulu". The article uses methods of selection, systematization, division into lexico-semantic and thematic groups, structural, descriptive, semantic grouping, synchronous analysis, and construction. The article examines from a historical and poetic point of view selected versions of one of the oldest cultural relics of the Kazakh people, "Kozy Korpesh-Bayan Sulu", with a comparison among themselves. It is known that this epic is a common heritage for all Turkic peoples. For example, the Altaians, Bashkirs, and Tatars have preserved several versions of this lyric epic. As for the Kazakh versions of the poem, this poem was first published in the third volume of V.Radlov’s work in 1870 "Samples of folk literature of Turkic tribes" and in 1876 by I.Berezin as part of the "Turkish Anthology". Many intellectuals, led by Sh. Ualikhanov, G.N.Potanin participated in publication and research of the epic. The results obtained during the study: 1) comparing the poetic language of the main versions of the epic, we find, as the most basic, ancient and artistic version, the version sung by Zhanak akyn; 2) issues related to the life and fate of the main characters of lyric-epic poems, such as "Kozy Korpesh-Bayan Sulu", "Kyz Zhibek" are identified; 3) it is proved who is actually a positive hero, since in different versions of the epic Sarybai and Karabai are perceived differently as positive and negative characters. Keywords: lyric epic, poetic corpus, poetic language, original, oppositional binary group.